Peritoneal lavage with coconut water in rats with abdominal sepsis and its effects in peritoneum - Borges, Kartagena Martins Barreto; Azevedo, Italo Medeiros; Celani, Lívia Medeiros Soares; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Purpose: This study aims to analyze the effects of peritoneal lavage with coconut water on the peritoneal reaction in abdominal sepsis model in rats. Methods: We used 12 male Wistar rats weighing between 310±15 g. The animals were randomly distributed into 2 groups, with 6 animals each. Abdominal sepsis was induced by cecum ligation and puncture (CLP) in both groups. Group 1 was subjected to peritoneal lavage three times with 5 ml of saline each time; Group 2 submitted to peritoneal lavage with 5ml of coconut water also three times. Peritoneal lavage occurred 24 hours after CLP. Twenty four hours after, liquid from peritoneal cavity was harvested for counting of bacterial colony forming units (CFU/mL) of both groups. Euthanasia was done with overdose of anesthesia. For histopathological analysis, fragments of the peritoneum were removed, and a score was applied to the degree of inflammation. RESULTS: Group 2 had a lower histopathological score (p<0.005) and the fluid obtained in the first peritoneal lavage showed a lower amount of CFU compared to group 1 (p <0.005). CONCLUSION: The peritoneal lavage with coconut water positively influenced the inflammatory response in fragments of the peritoneum and the amount of CFU of bacteria in the peritoneal fluid in an experimental model.